Nitrogen-Fixing Purple Nonsulfur Bacteria Originating from Acid Saline Soils of a Rice-Shrimp Farm - Anh, Nguyen Hoang; Xuan, Ly Ngoc Thanh; Xuan, Do Thi; Quang, Le Thanh; Khuong, Nguyen Quoc (Talenta Publisher, 2024)
The study was conducted to (i) isolate, select, and identify strains of purple nonsulfur bacteria (PNSB), which can fix nitrogen (N), from soil and water in a rice-shrimp integrated system, (ii) to determine the capacity of the selected potent PNSB strains in producing plant growth promoting substances. The isolation resulted in 57 pure PNSB strains from 36 soil samples and 36 water samples of rice-shrimp paddy fields in Thanh Phu - Ben Tre. Among them, 49 strains survived under pH 5.0 conditions, 24 of which grew well under microaerobic light (ML) and aerobic dark (AD) conditions in a basic isolation medium (BIM) containing NaCl 5‰. Two strains (S01 and S06) with the greatest N fixation were identified by 16S rRNA techniques as Rhodobacter sphaeroides. Their N production was 16.9 mg L-1 under the ML condition and 32.1 mg L-1 under the AD condition. Moreover, two R. sphaeroides S01 and S06 strains performed P solubilization at 0.382-2.954 mg L-1 from Al-P, 3.81-4.28 mg L-1 from Fe-P, and 3.87-4.74 mg L-1 from Ca-P, and production of plant growth promoting substances, such as IAA (12.3-15.5 mg L-1), EPS (1.09-1.58 mg L-1), siderophores (10.7-53.6%) and ALA (1.68-2.82 mg L-1) under both the incubating conditions.